Molecular Principles of Intrauterine Growth Restriction in Plasmodium Falciparum Infection - Seitz, Johanna; Morales-Prieto, Diana Maria; Favaro, Rodolfo R.; Schneider, Henning; Markert, Udo Rudolf (Frontiers in Endocrinology, 2019)
Malaria in pregnancy still constitutes a particular medical challenge in tropical and subtropical regions. Of the five Plasmodium species that are pathogenic to humans, infection with Plasmodium falciparum leads to fulminant progression of the disease with massive impact on pregnancy. Severe anemia of the mother, miscarriage, stillbirth, preterm delivery and intrauterine growth restriction (IUGR) with reduced birth weight are frequent complications that lead to more than 10,000 maternal and 200,000 perinatal deaths annually worldwide. P. falciparum can adhere to the placenta via the expression of the surface antigen VAR2CSA, which leads to sequestration of infected erythrocytes in the intervillous space. This process induces a placental inflammation with involvement of immune cells and humoral factors. Especially, monocytes get activated and change the release of soluble mediators, including a variety of cytokines. This proinflammatory environment contributes to disorders of angiogenesis, blood flow, autophagy, and nutrient transport in the placenta and erythropoiesis. Collectively, they impair placental functions and, consequently, fetal growth. The discovery that women in endemic regions develop a certain immunity against VAR2CSA-expressing parasites with increasing number of pregnancies has redefined the understanding of malaria in pregnancy and offers strategies for the development of vaccines. The following review gives an overview of molecular processes in P. falciparum infection in pregnancy which may be involved in the development of IUGR.